Recent advances in electrochemical determination of anticancer drug 5-fluorouracil - Totka Dodevska; Dobrin Hadzhiev; Ivan Shterev (International Association of Physical Chemists (IAPC), 2023)
Reliable, rapid, highly selective and sensitive analytical methods for the determination of antineoplastic agent 5-fluorouracil (5-FU) in human body fluids (blood serum/plasma and urine) are required to improve the chemotherapy regimen to reduce its toxicity and improve efficacy. Nowadays, electrochemical techniques provide a powerful analytical tool for 5-FU detection systems. This comprehensive review covers the advances in the development of electrochemical sensors for the quantitative determination of 5-FU, mainly focused on original studies reported from 2015 to date. We have summarized recent trends in the electrochemical sensor systems applied for the analysis of 5-FU in pharmaceutical formulations and biological samples, and critically evaluated the key performance metrics of these sensors (limit of detection, linear range, stability and recovery). Challenges and future outlooks in this field have also been discussed.